Bovine reproductive immunoinfertility: pathogenesis and immunotherapy - Gupta, Vinod Kumar; Mohanty, Tushar Kumar; Bhakat, Mukesh; Dewry, Raju Kumar; Katiyar, Rahul; Nain, Dipti; Shah, Nadeem; Sethi, Manisha; Rautela, Rupali; Singh, Mahak; Deori, Sourabh (Frontiers in Veterinary Science, 2023)
Infertility is one of the primary factors for cattle reproduction in the present scenario. Reproduction-related immunoinfertility mainly involves immunization against the antigens related to reproductive hormones (LHRH, GnRH, Gonadal steroids, PGF2α and oxytocin), spermatozoa, seminal plasma and ovum. Anovulation, delayed ovulation, sperm immobilization, failure of fertilization, prolonged uterine involution, extended calving interval, prolonged post-partum estrus and reduced conception rate could be a result of immunoinfertility that occur due to the blockage of receptor site by antibodies formed against hormones, sperm and ovum. Immunoinfertility can be treated in the animal by giving sexual rest to females, by using various reproductive technologies such as in-vitro fertilization, gamete intra fallopian tube transfer, and intracytoplasmic sperm injection, sperm washing and by treating the animals with immunomodulators such as LPS, Oyster glycogen, etc. This review summarizes the different causes of bovine reproductive immunoinfertility and amelioration strategies to overcome it.